Judicial Control Over Appropriation Decisions In Syrian Legislation An Analytical Study (Damascus University Journal for legal sciences, 2025)
Public utilities, as they represent the satisfaction of the basic public needs of individuals, are the reason for the existence of the public administration and its purpose. It has been granted the privileges of public law in order to ensure the smooth running of these utilities to the fullest extent, and to provide the services entrusted to them in the best possible way. Expropriation is one of the most important privileges owned by the public administration to obtain real estate necessary for the establishment and management of public utilities. It is the coercive sale imposed by the administration on individuals to give up their immovable property, when there is a need for those funds for the proper functioning of public utilities. It is a means that responds to the most important human rights, which is the right to property, which the constitution has preserved and protected by law. However, we find that expropriation in Syria differs from what it is in other countries, where successive legislation has immunized the expropriation decree from appeal or review before the judiciary, given that it will only take place It is required for the public interest and in return for fair compensation, and that it requires speedy completion and stability of interests, which justifies its immunization from judicial Control. Since the expropriation decision, like other administrative decisions, must be issued with its elements complete, and free from any defect of legality that may lose its legitimacy and respect by individuals, the role of the administrative judiciary has emerged as a protector of rights and freedoms, in monitoring the legitimacy of this decision through scrutiny. Its pillars, and the administration's consideration of the guarantees established for individuals during the issuance of its expropriation decision. The reality confirms that the administration is not always free from violating the rules and the law, which necessitates the necessity of effective judicial oversight in order to preserve one of the most important human rights (the right of individual property).
Keywords: State Council; Private Property; Expropriation Law; Public Benefit; Fair Compensation